1984
DOI: 10.1002/hon.2900020402
|View full text |Cite
|
Sign up to set email alerts
|

Non‐random chromosomal aberrations associated with multiple myeloma

Abstract: Myelomatous tissue from 30 patients was assessed for cytogenetic abnormalities and one-third showed chromosomal deletions, additions, and/or rearrangements. Evidence is presented that those cases with only normal cytogenetics represent metaphase cells of nonmyelomatous tissue. The findings of our abnormal cases when added to the 18 reported in two series by others show unique cytogenetic patterns are present in this disease. From analysis of these 27 banded cases of myeloma, we conclude: (1) cytogenetic abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Significantly, MYC rearrangements involving 1p13 , 6p21, 6q21 and 13q14 are recurrent in previous karyotypic analyses. 10, 46-49 …”
Section: Discussionmentioning
confidence: 99%
“…Significantly, MYC rearrangements involving 1p13 , 6p21, 6q21 and 13q14 are recurrent in previous karyotypic analyses. 10, 46-49 …”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies in multiple myeloma patients (prior to treatment) have revealed that the most commonly affected chromosomes have been Chr 1 and Chr 14 (59). Common abnormalities include chromosomal breakpoints (59)(60)(61)(62)(63) and deletions or duplications (59,64,65) of the chromosome ranging from lpll-35 and lq22-43. In addition, tumor samples from 10 Burkitt lymphoma patients had partial trisomy for Chr lq (62), bone marrow cells from a single patient with a plasma cell leukemia were carrying a translocation involving Chr 1 and Chr 6 (66), and 28 DLLC samples had chromosomal breaks at either 1p32-36 or 1p22 (67).…”
Section: Methodsmentioning
confidence: 99%
“…2 Also reported in isolated cases of ATL (Sadamori et al 1985). (1984) t(14;19)(q32;ql3) B-CLL II Bloomfield et al (1983); Ueshima et al (1985) Other translocations ML Bloomfield et al (1983); ATL Miyamoto et al (1984); Shiraishi et al (1985) B-PLL3 Pittman and Catovsky (1983) ; Sadamori et al(1983) PCL3 Ueshima et al (1983); Lewis and Mackenzie (1984) (1984) de la Chapelle and Lahtinen (1983); Testa et al (1984); LeBeau et al (1985) 16q 22 del (16) ; Davis et al (1984);Miller et al (1985) Chromosome 21 The breakpoint in 22q11 in chronic myeloid leukemia is distal to the breakpoint in t(8;22) in Burkitt lymphoma (Rabbits et al 1983;Emanuel et al 1984) o Band 22q11 is involved in variant translocations in CML and ALL (de la Chapelle and Berger HGM7) O Monosomy for entire chromosome 22 is much commoner than deletion (de la Chapelle and Berger HGM7).…”
Section: Regionmentioning
confidence: 99%
“…Trisomy 5 Multiple myeloma Liang et al (1979); Lewis and Mackenzie (1984) Monosomy for entire chromosome 5 is common in these disorders Lowenberg et al (1982) Suggested to be associated with marrow basophilia . Wilms' tumor-WAGR complex^I de la Chapelle and Berger (HGM7); Narahara et al (1984); Kondo et al (1984); Douglass et al (1985); Slater et al (1985) t ( 11 ; 14) Fukuhara et al (1983); Van den Berghe et al (1984); Ferti et al (1984) t(ll;14)(ql3.3;q32.3) ML I Fleischman and Prigogina (1977); Bloomfield et al (1983); 1lql3-q 14 Deletions, translocations ANLL-M4 and M5 II de la Chapelle and Berger (HGM7); IWCL IV (1984) t(10;11)(P14;ql3-ql4) II see chromosome 10 1 lq 14 del(11)(q 14) MDS I Swansbury and Lawler (1980); Swolin et al(1981); Mitelman et al (1981); Kardon et al (1982); Mufti et al (1982) Reported most commonly as a constitutional abnormality but homozygosity for del(11) and loss of normal 11 observed 2 in several tumors (Koufos et al 1984, Orkin et al 1984, Fearon et al 1984 Wilms' tumor, aniridia, genital anomalies, mental retardation Chromosome 11 continues on next page Tilly et al (1984); Becroft et al (1984); Prieto et al (1985); Workman et al (1985) Trisomy 11 Multiple myeloma Liang et al (1979); Philip et al (1980); Lewis and Mackenzie (1984) The same translocation has been observed in two cases of neuroepithelioma (Whang-Peng et al 1984b) (1983); Gibas et al (1984c); Delozier-Blanchet et al (1985) 12ql3-q22 dup(12)(ql3q22) ML II de la Chapelle and Berger (HGM7); …”
Section: Sporadic Recurrent Translocationsmentioning
confidence: 99%